2018
DOI: 10.3390/urbansci2030057
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production and Sanitary Risk along the Food Chain in Five Cities in Burkina Faso

Abstract: Abstract:Livestock is the third largest currency provider in Burkina Faso after gold and cotton. The objective of this study was to assess the socio-economic characteristics of actors, level of production and sanitary risks along the food chain of local fermented milk. A literature search and an investigation were conducted. Sphinx Plus 2 -V5 software was used for data processing and analysis. Results obtained show that milk processing is essentially a female activity and Fulani is the most active tribe in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…The poor quality fermented milk, unclean, and insufficient cleaning of milk equipments were among the most important sources of milk contamination. The milk is generally exposed to different contaminants when it transferred from one container to another, transported to consumers as well as retailers from the production site without cooling facilities, and with no proper milk containers [28,29]. In general, these high rates of microorganisms can be explained by the fact that traditional production is neither controlled nor regulated, as the majority of producers and distributors are not sufficiently informed about hygiene and risk management measures [6,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The poor quality fermented milk, unclean, and insufficient cleaning of milk equipments were among the most important sources of milk contamination. The milk is generally exposed to different contaminants when it transferred from one container to another, transported to consumers as well as retailers from the production site without cooling facilities, and with no proper milk containers [28,29]. In general, these high rates of microorganisms can be explained by the fact that traditional production is neither controlled nor regulated, as the majority of producers and distributors are not sufficiently informed about hygiene and risk management measures [6,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies were found that animals were alimented by contaminated feed and waiting time for milking after administration of antibiotics was not respected (Wanniatie et al, 2019). Similarly, we have also noticed the dirty environments of sales and transformations, the washing of materials used in traditional gold panning sites at watering points of animals (Cissé et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…The production and sale of Bîisim missiga is an important strategy implemented in the country. Indeed, milk is a highly valued food whose nutritional and economic contribution within producing households is no longer demonstrated (Boko et al, 2016;Cissé et al, 2018). Several products are derived from milk processing, the best known in Burkina Faso are pasteurized milk, Bîisim missiga, butter (solid or liquid) and cheese (Hamadou and Sanon, 2005;Cissé et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations